The interplay between oral microbes and immune responses - Liu, Yuan; Qv, Wenting; Ma, Yinchao; Zhang, Yuying; Ding, Chong; Chu, Ming; Chen, Feng (Frontiers in Microbiology, 2022)
Oral microbes play a critical role in maintaining oral homeostasis. Microbial dysbiosis promotes disease pathogenesis through several mechanisms. Recent studies have revealed that microbial imbalance and sustained inflammation are involved in disease progression. The adverse interaction triggered by a host immune response to microorganisms can lead to oral and systemic diseases. Here, we reviewed how oral microbes communicate with hosts during the development of local and distant inflammation. Elucidation of these processes may reveal future directions in this field and the potential targets of novel biological therapies for oral and systemic diseases.